Molecular Structure, MESP, HOMO-LUMO, and Vibrational Analysis of β-Asarone Using Density Functional Theory - Joshi, Bhawani Datt; Chaudhary, Paras Nath (Kathmandu University Journal of Science, Engineering and Technology, 2013)
Medicinal Plants have always had an important place in the therapeutic armoury of mankind. β-Asarone mainly found in Acorus calamus L., Araceae, is one of the main bioactive constituents of its essential oil. In this communication, we have presented the geometry optimization, molecular electrostatic potential surface, frontier orbital energy gap and vibrational wavenumbers of β-asarone using density functional theory (DFT/B3LYP) method employing 6-311G(d,p) basis set. A complete vibrational assignment has been done on the basis of an isolated molecule. The electronic transition has been calculated in the gas phase as well as in solvent environment (integral- equation formalism polarizable continuum model; IEF-PCM) using TD-DFT/6-31G basis set.